2015
DOI: 10.1159/000368502
|View full text |Cite
|
Sign up to set email alerts
|

Sclerostin Quo Vadis? - Is This a Useful Long-Term Mortality Parameter in Prevalent Hemodialysis Patients?

Abstract: Background/Aims: Cardiovascular calcification contributes to the increased mortality in hemodialysis patients. Sclerostin was identified as an antianabolic bone factor causing soft tissue calcification. Data on prospective large-scale studies associating sclerostin with mortality in hemodialysis patients are so far inconsistent. Methods: In our multicenter prospective longitudinal study following hemodialysis patients, we assessed the associations of sclerostin and bone remodeling markers with long-term mortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 38 publications
(48 reference statements)
0
18
0
Order By: Relevance
“…Some showed that serum sclerostin levels had no association with all-cause mortality [21][22][23], and two showed a significant negative association with all-cause mortality [24,25]. A recent quantitative meta-analysis concluded that no significant association existed between sclerostin levels and either all-cause mortality or CVD mortality [26].…”
Section: Discussionmentioning
confidence: 99%
“…Some showed that serum sclerostin levels had no association with all-cause mortality [21][22][23], and two showed a significant negative association with all-cause mortality [24,25]. A recent quantitative meta-analysis concluded that no significant association existed between sclerostin levels and either all-cause mortality or CVD mortality [26].…”
Section: Discussionmentioning
confidence: 99%
“…Secondary hyperparathyreodism is often seen in patients with end-stage kidney disease [24][25][26][27][28]. However, there are meanwhile well established therapeutic options to cope with this condition such as reducing phosphate reupsorption by phosphate binders, vitamin D treatment, treatment with calimimetitics such as cinacalcet and finally removal (partially or total) of the parathyroid gland [29].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, reports from pre-dialysis CKD studies showed that higher serum ALP levels are associated with increased all-cause mortality [3][4][5]. In dialysis patients, elevated serum ALP levels are also associated with increased mortality, independent of liver and bone metabolism parameters in both, hemodialysis (HD) and peritoneal dialysis patients [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%